Soluble plasma VE-cadherin concentrations are elevated in patients with STEC infection and haemolytic uraemic syndrome: a case–control study. Issue 3 (10th March 2015) - Doulgere, Julia; Otto, Benjamin; Nassour, Maher; Wolters-Eisfeld, Gerrit; Rohde, Holger; Magnus, Tim; Wagener, Christoph; Streichert, Thomas
Abstract : Objectives: To investigate whether the adherens junction protein vascular endothelial cadherin (VE-cadherin) is released during Shiga toxin 2 producing Escherichia coli (STEC) infection with haemolytic uraemic syndrome (HUS) and thus could be used to assist diagnosis. Design: Using data from the large 2011 STEC outbreak in northern Europe, we determined VE-cadherin plasma concentrations in 356 patients distributed over three patient cohorts: patients with STEC infection accompanied by HUS (STEC-HUS), STEC patients without HUS (STEC) and control patients with diarrhoea but without STEC infection. We then looked for associations between VE-cadherin concentrations and disease severity defined by changes in lactate dehydrogenase, haemoglobin, creatinine, platelet count, haptoglobin and neurological symptoms. Setting: This study was conducted at the University Medical Center Hamburg-Eppendorf, Germany. Participants: 79 STEC-HUS patients, 77 STEC patients and 200 control patients were enrolled in the study. Results: We analysed 864 specimens (207 STEC, 449 STEC-HUS and 208 controls) in total. At admission, VE-cadherin concentration tended to be lower in STEC-HUS patients compared to other patients. However, HUS patients later showed an increase in VE-cadherin concentrations with prolonged elevation beyond remission. This pattern clearly differs from that observed in non-HUS patients. Conclusions: VE-cadherin concentrations are elevated in STEC-HUS patients and might be a biomarker reflecting endothelial damage in patients with HUS.